PERLINDUNGAN HUKUM TERHADAP PARA PIHAK DALAM PENGALIHAN PIUTANG ATAS NAMA (CESSIE) MELALUI MEDIA INTERNET - Kusuma Dewi, A.A. Ayu; Dharma Kusuma, A.A. Gede Agung (Kertha Semaya : Journal Ilmu Hukum, 2015)
In a society that is increasingly developed along with the rapid development oftechnology, people in meeting their needs often experience barriers. To establish a person'slife will always fight for everything in order to survive. If someone in sustaining life deadlockin meeting their needs, then someone will be able to perform a variety of ways one of which isby way of borrowing money. to date there has been no legal norms that regulate clearly thetransfer of receivables through the internet. With the aim to determine the legal protectionfor parties in receivables transfer agreement (cessie) via the Internet. This research is a kindof legal normative legal research that examines the written laws of the various aspects,namely "aspects of theory, history, philosophy, comparative, structure and composition,scope and content, consistency, overview and chapter by chapter, formality and bindingstrength a law. With the conclusion of Responsibility to the parties to the transfer agreementon behalf of the receivables (cessie) via the Internet is realized in terms of legal protectiongranted by the state through legislation (formal) to the citizens of the State. This can be seenin Article 613 Code of Civil Law, Article 19 of Act 42 of 1999 regarding fiduciary insurance.
Keywords: Protection Law, cessie, Internet media